Effect of phenol and sulphide on the reproduction of sexually maturing riverine cat fish Rita rita (Hamilton) - Das, Manas Kumar; Samanta, Srikanta; Saha, Keya; Bhowmick, Sanjoy; Srivastava, P. K.; Bandopadhyay, S. (Journal of the Inland Fisheries Society of India, 2019)
Sexually maturing riverine cat fish Rita rita were treated with sub-lethal levels of phenol and sulphide for 30 days to identify their effects on the gonadosomatic index (GSI), hepatosomatic index (HSI), cholesterol levels in the ovary and liver, and plasma 17 Î²-estradiol levels. Both the contaminants significantly decreased the GSI, size of the oocytes and the plasma 17 Î²-estradiol levels. Whereas a significant increase in the HSI and the cholesterol levels of the ovary and liver was evident. The increase in the levels of ovarian and hepatic cholesterol and the decrease in plasma 17 Î²- estradiol and GSI indicate impaired steroidogenesis and ovarian maturation in the exposed fish.Keywords Phenol, sulphide, reproduction, cholesterol, 17 Î²-estradiol, gonadosomatic indexÂ